Code Mixing in Online English Classes: A Qualitative Analysis of Teacher-Student Communication at Junior High School Level: Campur Kode dalam Kelas Bahasa Inggris Online: Analisis Kualitatif Komunikasi Guru-Siswa di Tingkat Sekolah Menengah Pertama - Imanudin, Faldi Jihad; Astutik, Yuli (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the utilization of code mixing in online English classes at the junior high school level, focusing on the type and frequency of code mixing employed by both the English teacher and students. Data were collected through video recording and observation at SMPN 3 Candi in Sidoarjo, employing a qualitative research design. Muysken's theory (2000) was used to analyze the variation of code mixing in the English class, which included alternation, insertion, and congruent lexicalization. The most prevalent type of code mixing observed was alternation, used as an alternative teaching strategy to enhance student comprehension. The study involved a non-participant observation approach, with data categorized by dates and dialogues classified based on code mixing types. Results indicated that alternation was the dominant code mixing type used by the teacher and students, facilitating improved understanding of English materials. The research concludes that code mixing serves as a valuable pedagogical tool in the learning process, acting as a bridge between students and teachers. The implications suggest further exploration of code mixing in educational institutions and the development of teaching techniques based on the findings to enhance language learning experiences. Highlight: The study examines code mixing patterns in online English classes at the junior high school level, focusing on the usage by teachers and students. The most frequently used code mixing type is alternation, which serves as an effective alternative teaching strategy for facilitating student comprehension. Code mixing functions as a bridge between teachers and students, enhancing the learning process and aiding in understanding English materials. Further research in educational institutions can explore its benefits and potential for developing effective teaching techniques. Keyword: Code Mixing, Online English Class, Junior High School, Alternation, Educational Institution.